Interrater Reliability, Acceptability, and Practicality of Real-Time Video Pediatric Gait, Arms, Legs, and Spine for Musculoskeletal Assessment of Children During Telemedicine Visits. - KENİŞ COŞKUN, ÖZGE (My University, 2022)
Background/Objective With the COVID-19 (coronavirus disease 2019) pandemic, telemedicine applications gained momentum, and clinicians tried to develop various musculoskeletal examination methods to be used in telemedicine visits. The aim of this study is to investigate the interrater reliability, acceptability, and practicality of the real-time video Pediatric Gait, Arms, Legs, and Spine (v-pGALS) assessment used in the evaluation during the telemedicine visit. Methods The study was designed as cross-sectional. Twenty school-aged children who presented to outpatient clinics with musculoskeletal complaints were included. For interrater reliability, the children were evaluated by face-to-face examination with v-pGALS, and then the child was reevaluated by another physiatrist with real-time evaluation (online video call) with the help of a parent. For acceptability, the time taken and the discomfort caused were evaluated by patients/parents with the smiley face visual analog scale, whereas to assess practicality, the ratio of completeness to duration of examination completion was recorded. Results kappa coefficient of the agreement was found to be 0.88 between the results of the face-to-face examination and online video examination, suggesting very good agreement between the 2 raters. Acceptability of v-pGALS by parents and patients was high; 60% of children and 80% of parents found the duration of examination acceptable, and 70% of the patients and 95% of parents reported no discomfort caused by examination. The duration of face-to-face examination was 5.75 +/- 1.29 minutes, whereas the duration of online examination was 15.81 +/- 4.9 minutes. Conclusions Video pGALS is a reliable, acceptable, and practical examination system that can be used for musculoskeletal assessment of children in telemedicine visits.
Keywords: ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); child; musculoskeletal examination; pediatric clinical assessment; telemedicine; v-pGALS; TRANSLATION; PGALS